City, Citizen, Citizenship, 400–1500 (Springer Nature, 2024)
This open access book explores how medieval societies conversed about the city and citizen in texts, visual imagery and material culture. It adopts a long-term, interdisciplinary, and cross-cultural perspective, bringing together contributions on the early, high, and later Middle Ages, covering both the medieval East and West, and representing a wide variety of disciplinary angles and sources. The volume is first and foremost about medieval perceptions and their articulation in text, image and material form. The principal focus is not on cities or citizenship per se, but on those who used such concepts, wrote about them, and visualized and depicted them. At the same time, the book seeks to address why the city remained such a salient concept also in non-urban contexts – the periphery, the desert, the monastery – and how medieval thinking on the ideal city and civic community could involve denunciation of the earthly city and its institutional trappings. It thus pushes scholarly boundaries, but also seeks to escape deeply entrenched notions of citizenship as either a form of political participation or legal status.